2013
DOI: 10.1007/s00403-013-1421-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutational founder effect in recessive dystrophic epidermolysis bullosa families from Southern Tunisia

Abstract: Dystrophic epidermolysis bullosa (DEB) is a group of heritable bullous skin disorders caused by mutations in the COL7A1 gene. One of the most severe forms of DEB is the severe generalized [recessive dystrophic epidermolysis bullosa (RDEB-SG)] subtype, which is inherited in an autosomal recessive manner. This subtype is most often due to COL7A1 mutations resulting in a premature termination codon on both alleles. We report here, the molecular investigation of 15 patients belonging to 14 nuclear families from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Direct sequencing of all COL7A1 coding regions might be challenging as they encompass 118 exons, and more than 70 polymerase chain reaction primer pairs are necessary for the amplification of all coding regions3. In addition, the genetic heterogeneity and the important number of “private mutation” make the genetic diagnosis more challenging even in endogamous populations4. WES has led to the identification of a considerable number of pathogenic mutations in monogenic Mendelian disorders, including skin pathologies5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct sequencing of all COL7A1 coding regions might be challenging as they encompass 118 exons, and more than 70 polymerase chain reaction primer pairs are necessary for the amplification of all coding regions3. In addition, the genetic heterogeneity and the important number of “private mutation” make the genetic diagnosis more challenging even in endogamous populations4. WES has led to the identification of a considerable number of pathogenic mutations in monogenic Mendelian disorders, including skin pathologies5.…”
mentioning
confidence: 99%
“…This is to our knowledge the first study of a Libyan patient. Our previous studies showed that despite mutational heterogeneity of HEB, some mutations are likely founder and closed to specific geographic regions4. Therefore, screening of c.2701+1G>A mutation could assist in determining the molecular aetiology of HEB among eastern Libyan patients.…”
mentioning
confidence: 99%